2017
DOI: 10.1039/c6mb00699j
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA sequencing revealed dysregulated piRNAs in Alzheimer's disease and their probable role in pathogenesis

Abstract: PIWI-interacting RNAs (piRNAs), ∼23-36 nucleotide-long small non-coding RNAs, earlier believed to be germline-specific, have now been identified in somatic cells including neural cells. However, piRNAs have not yet been studied in the human brain (HB) and Alzheimer's disease (AD)-affected brain. In this study, by next-generation small RNA sequencing, 564 and 451 piRNAs were identified in the HB and AD-affected brain respectively. The majority of the neuronal piRNAs have intronic origin wherein primary piRNAs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 52 publications
8
98
0
Order By: Relevance
“…Two piRNAs, including DQ599147 at CTC1 (FC=1.8, p=0.048) and DQ597974 near C11orf87 (FC=2.0, p=0.031), expressed in significantly higher levels in cases than controls (Table S2) replicated previous findings (Roy, et al, 2017). …”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Two piRNAs, including DQ599147 at CTC1 (FC=1.8, p=0.048) and DQ597974 near C11orf87 (FC=2.0, p=0.031), expressed in significantly higher levels in cases than controls (Table S2) replicated previous findings (Roy, et al, 2017). …”
Section: Resultssupporting
confidence: 84%
“…Across transcriptome, only 5 percent of piRNAs can be mapped to protein-coding genes (Brennecke, et al, 2007); however, among the AD-associated piRNAs identified in this study, 41% are enriched in the protein-coding genes, suggesting a strong correlation among these genes, piRNAs and AD. Sequences of the AD-associated piRNAs are complement to or close to these protein-coding genes, and thus, the piRNAs are most likely to target and regulate these nearest genes by sequence complementarity (Roy, et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…27,45 It is also observed that specific set of mRNAs are actively selected for piRNA production as a requirement for various regulatory purposes. 27,45 It is also observed that specific set of mRNAs are actively selected for piRNA production as a requirement for various regulatory purposes.…”
Section: Pirnas Derived From Pcgsmentioning
confidence: 99%
“…The most developed treatment option includes surgical resection and adjuvant-chemotherapy to which they respond poorly, leading to local recurrence and distant metastasis. New treatment procedures like targeted therapies and development of diagnostic markers need to be augmented for tackling this early metastatic cancer possibly by harnessing the potential of small noncoding RNAs (ncRNAs) such as microRNAs (miRNAs) and piwiinteracting RNAs (piRNAs) [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%